Pola Ketergantungan Pariwisata di Taman Nasional Komodo - Kurniawan Agung, Dhika (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The designation of Komodo National Park as a super priority destination, the zoning policy and the discourse of closing the area have limited the access of people living in the National Park area. The community's main livelihood as fishermen is limited to certain zones. This qualitative research uses qualitative data collection techniques, namely (1) Participant observation (2) In-depth interviews; (3) Document study. This research uses the snowball sampling method in determining informants. The results show that changes in environmental management are not only limited to changing the environment, but also forming new subjects in the community. The main livelihood of the community as fishermen is limited to certain zones, slowly fishermen's livelihoods are uncertain results, making people switch livelihoods to the tourism sector. The high standard of tourism sometimes makes some local tourism actors unable to keep up, resulting in dependence on capital and human resources from developed country investors. The low bargaining position of the community occurs due to the monopoly of the tourism business from investors.